EFFECT OF MAGNETIC FIELD ON THE PLASMA CHEMICAL PROCESS OF COMBUSTION OF LIQUID COMPOSITE BIOFUELS - Strebkov, D.; Kozhevnikov, Y.; Egorov, Y.; Schekochikhin, Y.; Nikolaev, V. (Energy and Automation, 2016)
In the article the question of the optimal location of plasma microwave emitters in the combustion chamber for burning composite biofuels is considered. The are physical processes of interaction of plasma particles with an external magnetic field. Taking into account based on the above solutions for designing the plasma torch are proposed